Berücksichtigung von Genderaspekten in den neuen gestuften Studiengängen in der Raumplanung - Zibell, Barbara (Raumforschung und Raumordnung | Spatial Research and Planning, 2008)
The article analyses in how far the new tiered degree programmes of spatial planning, which have been developed within the so-called „Bologna Process”, are containing any gender contents or modules. This examination includes the German universities of Cottbus, Hamburg, Berlin, Dortmund and Kaiserslautern. p ]The author points out that gender traditions are proceeded where they already have been existent. However, if those traditions have not been existent before, universities did not establish any gender aspects in the course of the reforms. Finally, it is suggested that sustainable spatial development has to be supported by gender aspects. Therefore, universities are advised to further develop those aspects within their study programme.
Keywords: gender equality; gender mainstreaming; accreditation; degree programs of spatial planning in Germany; requirement of innovation in (higher) education